IDENTIFIKASI DAN INVENTARISASI USAHA AGRIBISNIS DI SEKITAR KAWASAN HUTAN KECAMATAN SEJANGKUNG KABUPATEN SAMBAS KALIMANTAN BARAT - RAKHMAD HIDAYAT, ABDUL HAMID A. YUSRA, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2012)
ABSTRACTThe aims of this research were: (1)to determine the types of existing agribusiness around forest areas, (2)to determine the agribusiness system that goes around forest areas (3)To determine the factors that affect the farm income communities around the forest areas in sub district Sejangkung.The results showed that (1)Traditional and semi subsistance farming activities that carried out by the forest communities is food crops (rice)and poultry. Commercial farming is rubber and coconut. (2) The style farming communities around the forest areas still hereditary, traditional, using family labor, own capital and marketed their crops to middlemen or directly sold to the market sub-district or district level.(3) Revenue farmingcommunities around the forest are included in the category of lower middle income. The lowest income level is Rp. 500.000/month and the highest is Rp. 3.000.000/month, with an average total income is Rp. 1.436.667/month.Based on the results of the regression analysis, the factors that affect farm income are land area and capital. Factors that not affect the farm income are age, level of education, family size, farming experience, and labor.Keywords: Agribusiness, Community around forests, Farmers income